SISTEM IDENTIFIKASI SAMPAH ANORGANIK BERBASIS IOT (Internet of Things) MENGGUNAKAN METODE SAW (Simple Additive Weighting) - Wijaya, Anderias Eko; Rokhman, Febriana Nur (STMIK Subang, 2023)
Inorganic waste is one of the environmental issues that needs to be effectively managed. An Internet of Things (IoT)-based system using the Simple Additive Weighting (SAW) method is implemented to provide a solution for the more efficient management of inorganic waste. This system utilizes sensors connected to the IoT network to detect and identify the types of inorganic waste entering a specific area. The SAW method is employed to assign weights to each criterion applied in the identification process of inorganic waste, such as type, weight, and physical condition. The system assesses based on the predefined criteria weights, enabling high-accuracy categorization of inorganic waste. Identification results can be accessed in real-time through the IoT platform Thingspeak, allowing for quick monitoring and analysis. Implementing this system is expected to positively contribute to the management of inorganic waste, facilitating more efficient collection, categorization, and overall waste handling. Moreover, adopting IoT technology and the SAW method in this system is envisioned to provide sustainable solutions in waste management efforts to support environmental sustainability.